Clinical and Epidemiological Characterization of Ophidic accidents in the General Hospital, Boa Vista, Roraima (Research, Society and Development, 2022)
Introduction: Snakebite envenomation are considered a serious public health problem in Brazil. This research aimed to describe the clinical-epidemiological aspects of snakebite envenomation in a reference hospital in Boa Vista, Roraima. Method: This is a retrospective observational, descriptive cross-sectional study about the patients’ medical records who were bitten by snake and admitted at the General Hospital of Roraima (HGR) for snakebite envenomation in 2020. Results: From the analysis of 69 medical records, it was found that snakebite envenomation occurred with higher prevalence in the municipality of Boa Vista, zone of occurrence ignored, in the daytime period and in the months of January and December. The epidemiological profile was composed of individuals mostly male, young and young adults and, lastly, in browns. Regarding the clinical profile it was observed that the most affected anatomical region was the foot, the time from the bite to the care was ignored, botropic envenomation and mild and moderate severity. Conclusions: This research allowed us to describe the clinical and epidemiological profile of snakebite envenomation recorded at the HGR in 2020 and identified that the involvement occurs mainly in male of an economic active age, during the daytime, brown, from Boa Vista and are botropic accidents, light and moderate severity in the foot. Despite the ignored data, it was possible to describe the current panorama of odisidic accidents attended in the HGR. However, further work is needed and may help in understanding the distribution of these accidents in Roraima.